2018
DOI: 10.1007/s40094-018-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensor utilizing a ternary photonic crystal with a polymer layer sandwiched between Si and SiO2 layers

Abstract: Recently, one-dimensional periodic ternary photonic crystals have shown outstanding properties when compared to onedimensional periodic binary photonic crystals. In this work, a ternary photonic crystal is proposed as a temperature sensor. The structure of the ternary photonic structure is considered Si/polymer/SiO 2. The transmission spectra of the proposed ternary photonic structure are studied for different temperatures. It is observed that as the temperature increases, the transmission peak shifts toward h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…1. Recently, the periodic ternary 1D-1DPC structures have attracted the researchers attention due to their high sensing performance compared with the binary systems 41,42 . For refractive index detection, the target solution is injected inside the flow cell in contact with the top surface of the PSi-1DPC in order to allow for the solution to fill the pores as shown in the schematic diagram of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1. Recently, the periodic ternary 1D-1DPC structures have attracted the researchers attention due to their high sensing performance compared with the binary systems 41,42 . For refractive index detection, the target solution is injected inside the flow cell in contact with the top surface of the PSi-1DPC in order to allow for the solution to fill the pores as shown in the schematic diagram of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The glass transition temperature of PS was reported as 100 • C, and the nominal RI of PS is 1.59 at room temperature [29,32]. The sensing head with the PS coating was prepared by using the simple dip coating method.…”
Section: Sensor Fabricationmentioning
confidence: 99%
“…Various research on the temperature sensors with thermosensitive polymers has been conducted as well. For instance, Rong et al explored the polyvinyl alcohol (PVA) polymer for the application to the Fabry-Perot interferometer sensor [21], Romano et al developed a polydimethylsiloxane (PDMS) coated microfiber mode interferometer sensor [23], Salunkhe et al demonstrated the Fabry-Perot interferometer sensor with polycarbonate (PC) and poly (methyl methacrylate) (PMMA) [28], EI-Amassi et al applied the polystyrene (PS) for the temperature sensor with a photonic crystal fiber [29], and Esposito et al explored the PS coated LPG for temperature sensing [30]. It is acknowledged that the change of the thermal optic coefficient is the prime motive for the temperature-derived index change in the polymer, which plays a crucial role in determining the device performance; thus achieving this feature has been a targeted research goal for optical fiber temperature sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abadla et al [15] proposed ternary PCs that can offer better performance over the binary ones. In more recent, ternary structures with new chosen materials are under investigation for novel and efficient kind of tuning of the PBGs [16][17].…”
Section: Introductionmentioning
confidence: 99%